2010
DOI: 10.1007/s12192-009-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum heat shock protein 27 antigen and antibody levels appear to be related to the macrovascular complications associated with insulin resistance: a pilot study

Abstract: Heat shock protein 27 (Hsp27) is over-expressed when cells are exposed to stressful conditions that include oxidative stress. Oxidative stress has been implicated in the pathogenesis of cardiovascular disease (CVD), diabetes and insulin resistance. We have investigated the concentrations of serum Hsp27 antigen and antibodies in subjects from different glycaemic categories, who either did or did not have established CVD. Serum Hsp27 antigen and antibody levels (immunoglobulins M and G (IgM and IgG)) were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In addition, serum anti-Hsp27 antigen and antibody titers (IgM and IgG) have been reported to be related to the presence of cardiovascular complications in patients with glucose intolerance. This latter finding is consistent with the present findings as we have found a significant difference in the prevalence of diabetes mellitus among the groups, with the highest rate in the CAD + group (Pengiran Burut et al 2010). In the present study, serum anti-Hsp 27 titers in the CAD − group were higher than those in the control subjects but lower than those of CAD + group.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, serum anti-Hsp27 antigen and antibody titers (IgM and IgG) have been reported to be related to the presence of cardiovascular complications in patients with glucose intolerance. This latter finding is consistent with the present findings as we have found a significant difference in the prevalence of diabetes mellitus among the groups, with the highest rate in the CAD + group (Pengiran Burut et al 2010). In the present study, serum anti-Hsp 27 titers in the CAD − group were higher than those in the control subjects but lower than those of CAD + group.…”
Section: Discussionsupporting
confidence: 94%
“…Restriction stress increases the production of Hsp70, MCP-1, PAI-1, and monocyte adhesion but decreases adiponectin in mice [163]. The levels of Hsp27 antigen and antibody in serum of diabetic patients are associated with cardiovascular complications and insulin resistance [164]. Oxidized LDL (oxLDL) has been considered as a circulating marker for coronary artery disease [165].…”
Section: Metabolic Disorders and The Stress Responsementioning
confidence: 99%
“…They suggested that the release of HSP27 IgM antibody into circulation may lead to formation of immune complexes. This may be one reason for the clearance of released HSP27 in patients with acute coronary syndromes (32). We did not evaluate Hsp27 IgM antibody titers in this study but found similar serum HSP27 IgG antibody levels in MetS+ and MetS-group.…”
Section: Discussionmentioning
confidence: 66%